Detection of hepatitis B surface antigen by immunoassay using magnetite nanoparticles binding hepatitis B surface antibody. Issue 4 (4th July 2019) - Thanh, Bui Trung; Hai, Tran Hoang; Van, Pham Hung; Minh Tung, Le; Lee, Jaeryeong
ABSTRACT: The detection of hepatitis B surface antigen (HBsAg) with an immunoassay using magnetite nanoparticles (NPs) that bind hepatitis B surface antibody (anti-HBs) was investigated. Magnetite NPs with an average size of 32 nm were synthesized and functionalized using tetraethyl orthosilicate, 3-aminopropyltriethoxysilane, glutaraldehyde, and streptavidin. The functionalized NPs were conjugated with biotinylated anti-HBs to capture HBsAg. HBsAgs were detected with a sensitivity, specificity and agreement of 98%, 97%, and 97.5%, respectively, when compared to the rapid test. In addition, the novel method could also enrich HBsAgs, using different tube sizes and can facilitate amplification for the detection of microorganisms.